A traumatic ulnar artery aneurysm in an infant - Odajima, Rika (J Surg Case Rep, 2021)
Ulnar artery aneurysm is very rare in infancy. Only a few reports have been done. We report an 8-month-old baby with true ulnar artery aneurysm on her hypothenar eminence. She had no specific past medical history, but an episode of falling. We resected the pulsating mass compressing the ulnar nerve, utilizing a surgical microscope. Reconstruction of the vascular deficit was not performed. She presented no functional deficit of the hand and no evidence of growth disturbance so far. As hypothenar eminence is a susceptible part for repetitive strikes, and as vein is fragile to the pressure, bypassing arterial route with vein graft is not recommended unless there is no other option.